Procedures Review of Vehicles Transport In KMP. Uma Kalada Kupang – Rote Tracking, East Nusa Tenggara - Doharman Lumban Tungkup; Paulina M Latuheru; Martin Alan Buana (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2019)
The ferry port of Bolok is contained in Kupang district connects the island in East Nusa Tenggara province which has a very strategic position and has a huge economic potential to support the economy in the province of East Nusa Tenggara. In the security and safety of the transportation system highly favored as a form of good service delivery. Safety is intended not only to users of services, but also to the ship operator. As well as setting up and handling of the transport vehicles on board. The better regulation and vehicle handling on board the better the level of security and safety of vehicles on board and vice versa. The setting and handling of the transport vehicle in good ship for user / owner of the vehicle, as well as for the security and safety of vehicles on board and are not harmful to the operator of the vessel that can be done by means of an approach based on the arrangement of the vehicle by placing a distance between the vehicle safe and mounting strap vehicle (lashing) contained in the Minister of Transportation Regulation Number 115 of 2016 on procedures for the transport of vehicles on board.